Body size modifies the relationship between maternal serum 25-hydroxyvitamin D concentrations and gestational diabetes in high-risk women. Issue 3 (March 2018) - Valkama, Anita; Meinilä, Jelena; Koivusalo, Saila; Lindström, Jaana; Rönö, Kristiina; Tiitinen, Aila; Stach-Lempinen, Beata; Kautiainen, Hannu; Viljakainen, Heli; Andersson, Sture; Eriksson, Johan
Abstract Obesity increases the risk of low 25-hydroxyvitamin D (25(OH)D) concentrations and gestational diabetes (GDM). We explored whether the association between GDM and change in 25(OH)D concentrations measured in the first (7–18 wk) and second (20–27 wk) trimesters of pregnancy is dependent on maternal BMI. The study was a prospective study of 219 women with BMI of ≥30 kg/m2, a history of GDM, or both. The participants were stratified by first-trimester BMI: BMI of <25.0, 25.0–29.9, 30.0–34.9, and ≥35 kg/m2 . In the BMI group ≥35 kg/m2, those who did not develop GDM during the follow-up showed higher increase in serum 25(OH)D concentrations compared with women who developed GDM (43.2 vs. 11.5%;P < 0.001). No associations between 25(OH)D concentrations and GDM were observed in other BMI groups. These findings give an important aspect of the role of maternal body size in the association between vitamin D and GDM in high-risk women.